Transforming Africa’s Food System with Digital Technologies - Badiane, Ousmane; Glatzel, Katrin; Araba, Debisi (2019)
Ousmane Badiane, Katrin Glatzel, and Debisi Araba POLICY SEMINAR Transforming Africa’s Food System with Digital Technologies Co-Organized by the Malabo Montpellier Panel and IFPRI NOV 26, 2019 - 09:30 AM TO 11:00 AM EST